2009
DOI: 10.1016/j.jmatprotec.2008.03.002
|View full text |Cite
|
Sign up to set email alerts
|

A microstructural and low-cycle fatigue investigation of weld-repaired heat-resistant cast steels

Abstract: WeldingCracking Low-cycle fatigue a b s t r a c tThe multi-pass weld-repair of heat-resistant cast steels is carried out using an automated shielded metal arc welding (SMAW) process, with various filler materials and pre-heating at 400 • C. Specimens weld-repaired with a filler material more resistant than the heat-resistant cast steel (over-matching) generally crack within the base metal following the tenth filling pass, whereas specimens buttered with a soft alloy prior to welding remain free of cracks.The h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Fatigue behavior of aluminum alloys welded by conventional process has been investigated by some authors (Ambriz et al 2010b;Branza et al, 2009;Seto et al, 2004). In terms of fatigue behavior considering FSW, some interesting studies have been published (Matic & Domazet, 2005, Chiarelli et al, 1999, James & Paterson, 1998.…”
Section: Fatigue Crack Growthmentioning
confidence: 99%
“…Fatigue behavior of aluminum alloys welded by conventional process has been investigated by some authors (Ambriz et al 2010b;Branza et al, 2009;Seto et al, 2004). In terms of fatigue behavior considering FSW, some interesting studies have been published (Matic & Domazet, 2005, Chiarelli et al, 1999, James & Paterson, 1998.…”
Section: Fatigue Crack Growthmentioning
confidence: 99%
“…This method allowed, under special conditions, to prevent cracking during weld-repair of 20 mm deep V-grooves. However, the fatigue life time of such repairs was very low [9], so other weld-repair techniques have to be investigated for weld-repair SPF dies.…”
Section: Discussion and Improvement Of Weld-repair Methodsmentioning
confidence: 99%
“…However, recent works have shown that weld repair samples obtained with buttering technique have very low fatigue life time, so this repair process is not convenient for SPF dies [9].…”
Section: Introductionmentioning
confidence: 99%
“…Fatigue behavior of aluminum alloys welded by conventional process and MIEA has been investigated (Ambriz et al 2010b;Branza et al, 2009;Seto et al, 2004). Fig.…”
Section: Fatigue Crack Growth (Fcg)mentioning
confidence: 99%